Pancreatic hypofunction in extrahepatic portal venous obstruction. Issue 3 (March 1980) - Webb, L; Smith-Laing, G; Lake-Bakaar, G; McKavanagh, S; Sherlock, S
Abstract : Pancreatic function was studied in 29 patients with extrahepatic portal venous obstruction, and 30 age-matched controls. The aetiology of the portal venous obstruction was known in 20 out of 29 patients. No patient had a history of pancreatitis. Serum trypsin, both fasting and for 120 minutes after a Lundh meal, was significantly lower in the patients than in controls (P less than 0.005). 5/28 (18%) patients had reduced fasting serum trypsin levels and in 5/14 trypsin was abnormal after a Lundh meal. Mean fasting serum glucose (3.8 +/- ).49 mmol/l was significantly higher than in control subjects (mean 3.4 +/- 0.42 mmol/l) (P less than 0.05). After 100 g glucose orally, mean serum glucose at 180 minutes (5.26 +/- 1.58 mmol/l) was higher than the control value (3.96 +/- 1.45 mmol/l) (P less than 0.05), and 30 and 60 minutes serum C-peptide values were significantly lower (P less than 0.005). Pancreatic hypofunction found in these patients probably results from an abnormal portal circulation in association with mild pancreatic damage secondary to chronic venous congestion.